Fatty Acid Profiling of Fish Oil from Siro (Amblygaster sirm) and Tembang (Sardinella fimbriata) of West Sumbawa - Baiq Pebrianti Hidayati; Baiq Afriza Lia Fitri; Yuvita Lira Vesti Arista (Jurnal Penelitian Pendidikan IPA, 2026)
West Sumbawa waters possess abundant marine resources dominated by small pelagic fish species, including Siro (Amblygaster sirm) and Tembang (Sardinella fimbriata). However, information regarding the fatty acid profiles of these local fish remains limited. This study aimed to characterize the saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) in oils extracted from both species. Fish oil was extracted by maceration using an n-hexane:isopropanol solvent mixture (3:2, v/v), followed by fatty acid analysis using Gas Chromatography–Mass Spectrometry (GC–MS). The results showed that both fish oils were rich in long-chain polyunsaturated fatty acids (LC-PUFAs), predominantly docosahexaenoic acid (DHA, C22:6), reaching 23.25% in Siro and 21.04% in Tembang fish oil. Arachidonic acid (ARA, C20:4) was also detected at relatively balanced levels (9.66% and 9.52%, respectively), whereas eicosapentaenoic acid (EPA, C20:5) remained low (<1%). Palmitic acid (C16:0) predominated within the SFA fraction (~28.1%). These findings highlight the potential of fish oil from both species as a valuable source of functional ingredients for food fortification and nutraceutical applications